1986
DOI: 10.1152/ajpcell.1986.251.2.c274
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent markers to study membrane retrieval in antidiuretic hormone-treated toad urinary bladder

Abstract: Antidiuretic hormone (ADH) stimulation of toad urinary bladder causes fusion of intracellular vesicles called aggrephores with the apical plasma membrane of granular cells. Aggrephores contain intramembrane particle aggregates whose appearance in the apical membrane is believed to produce a large increase in its water permeability. ADH removal (ADH washout) is thought to cause the retrieval of aggrephores into granular cell cytoplasm. We studied granular cell uptake of dextran and horseradish peroxidase conjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Finally, the apical surface of ADH-stimulated bladders was exposed to an isosmotic solution containing lactoperoxidase at 5 mg/ml. Under these conditions there was no endocytosis (26,31), and peroxidase levels were the same as in cells from control bladders never exposed to lactoperoxidase/glucose oxidase (open circle in Fig. 2).…”
Section: Lactoperoxidase/glucose Oxidase Iodination Of the Apicalmentioning
confidence: 75%
See 2 more Smart Citations
“…Finally, the apical surface of ADH-stimulated bladders was exposed to an isosmotic solution containing lactoperoxidase at 5 mg/ml. Under these conditions there was no endocytosis (26,31), and peroxidase levels were the same as in cells from control bladders never exposed to lactoperoxidase/glucose oxidase (open circle in Fig. 2).…”
Section: Lactoperoxidase/glucose Oxidase Iodination Of the Apicalmentioning
confidence: 75%
“…Retrieval of granular cell apical membrane induced by ADH stimulation and removal has been studied by using a variety of fluid-phase markers, including HRP (6,10,26,31), ferritin (6), colloidal gold (7,10), and fluorescent dextran (31). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements ofuptake of fluorescent dextran or horseradish peroxidase (HRP) by granular cells were performed as previously described (27) using fluorescein-cnjugated dextran (F-dextran) and rhodamine-labeled horseradish peroxidase (R-HRP) at concentrations of20 and 5 mg/ml, respectively. The fluorescent marker was present in the mucosal solution in contact with the apical surface of granular cells during the uptake period as described in the text.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the presence of an osmotic gradient markedly increases granular cell uptake of enzymatic (25,26) and fluorescent (27) tracers during ADH stimulation and ADH removal. The tracers are found largely in tubular vesicles and multivesicular bodies (25).…”
Section: Introductionmentioning
confidence: 99%